Human Nature through Freudian Lenses. A Reading of "Ordinary People" (Robert Redford, 1980) - LAZAR, Gabriel (Studia Universitatis Babeș-Bolyai Dramatica, 2021)
The article highlights the Freudian approach applied in depicting the events ensuing in a family after a tragic accident – and the related psychoanalysis case, determined by a case of traumatic neurosis – as illustrated in Robert Redford’s movie Ordinary People. The elder son in the family dies in a boat accident, while his brother survives, unable to save him. Ridden with unconscious guilt, the brother tries to commit suicide. Later, he eventually starts an analysis that will bring to the surface his interpretation of the accident, unknown to himself, as the actual traumatic event. The emphasis is placed on a suggestion-free direction of the cure, as promoted by both Freud and Lacan, where the analyzand finds his own words and brings the trauma to memory, moving from a traumatic and compulsory reliving in the present to a remembering of something in the past which liberates the present.